Question

# Solve 3x+9y=24 and x+3y=8 by elimination I think I know the answer I just need clarification

Answer

These equations are equivalent; we can obtain one from the other by multiplying x+3y=8 by -3. Step-by-step explanation: 1. Recall that when multiplying an equation by a non-zero constant, we obtain an equivalent equation. 2. To obtain the equivalent equation, we multiply each term in x+3y=8 by -3: -3(x+3y) = -3(8) -3x - 9y = -24 3. Thus, the equation -3x - 9y = -24 is equivalent to x+3y=8. 4. To see why, we can solve both equations for y: y = (8-x)/3 y = (-24 - 3x)/9 We see that these expressions are equal, so any value of x that makes one true, also makes the other true.